On Hydrocanthus Say, 1823 (Coleoptera: Noteridae): description of a new species, two new synonyms and a key to Brazilian species - Guimarães, Bruno A. C.; Ferreira-Jr, Nelson; Miller, Kelly B. (Zootaxa, 2018)
A new species of Hydrocanthus Say, 1823 is described and illustrated, H. zimmermanni sp. nov. from Peru. A distinct pattern of prosternum and prosternal process setation and aedeagal features differentiate the new species from all other members of Hydrocanthus. Two new synonyms are established: H. rubiginosus Guignot, 1942 as junior synonym of H. debilis Sharp, 1882 (syn. nov.) and H. paludimonstrus Miller, 2001 as junior synonym of H. paraguayensis Zimmermann, 1928 (syn. nov.). In addition, a key to Brazilian species of Hydrocanthus is provided.